A Partially Decoupled Hybrid Manipulator with Separated Positions and Poses - Shuwei Qu; Fang Cheng; Zhihong Guo; Tengbo Qu (Jixie chuandong)
Hybrid manipulator has high bearing capacity of parallel manipulator and large operating space of series manipulator，so it has broad engineering application prospect. Taking the RPS parallel mechanism with decoupled characteristic as a module，a partially decoupled hybrid manipulator of series parallel hybrid structure is constructed. By distributing the drive chain on different platforms， the closed positive position solution is obtained. The independent position motion and pose motion are realized by establishing the virtual prototype. The theoretical results are consistent with the motion simulation results， and the displacement data points of the actuator change smoothly， it shows that the manipulator can relize complex operation motion. The motion inertia of the series parallel hybrid manipulator is reduced by this method， which provides an important theoretical basis for the application of the manipulator.